التناصّ في شعر محمود الورّاق / The Intertextuality in the Poetry of Mahmoud al-Warraq - bin ‘Aziz, Muhammad ‘Azizi (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2020)
مُلخَّص البحث التناصّ مصطلح نقديّ أدبيّ يرتبط بتفاعل النصوص الأدبية مع بعضها وما يترتّب على ذلك من دلالات في سياق النصوص الأدبية ذاتها. ويساعد استخدام التناصّ في دراسة النصّ على فهم العوامل الـمؤثّرة في بناء النصّ الأدبي التي تتضمّنُها نصوصٌ سابقة، فيسعى الناقد الأدبي إلى التنقيب عنه وإبرازه للقارئ عبر "عملية أركيولوجيا" تستهدف إلى التنقيب في طبقات النصّ الخفية؛ لأجل ذلك، يكشف البحث عن مصادر التناصّ لشاعر عبّاسي مُكثر في استخدام التناصّ في شعره وهو محمود الورّاق، ومن ثمّ سيُعيّن الباحث أنواع تناصّه الـمستخدمة. يتحقّق الهدافان السابقان باستخدام الـمنهج الوصفي والـمنهج التحليلي. ومن نتائج البحث أن محمود الورّاق استخدم ثلاثة مصادر في التناصّ؛ القرآن الكريم، والحديث النبوي الشريف، وأقوال البُلغاء والفُصحاء، ومن حيث أنواع التناصّ، فإنّه استخدم كلا نوعي التناصّ؛ الـمباشر وغير الـمباشر. الكلمات الـمفتاحية: التناصّ، النقد الأدبي، محمود الورّاق، العصر العبّاسي الأوّل، شاعر الحكمة والـموعظة. Abstract Intertextuality is a term used in literary criticism to discuss relationship between texts and the implications it brings to the meaning of the texts. The use of Intertextuality in text studies can enhance our understanding of factors influencing the writing of literary texts based on previous texts. Literary critics seek to explore intertextuality in texts and make it visible to readers through an “archaeology process” aimed at digging into the hidden layers of the text. This study investigates the sources of intertextuality in poems of Mahmoud al-Warraq, an Abbasid poet who is known to feature intertextuality extensively in his poetry. The study also aims to identify the types of intertextuality used in his poetry. Both of those goals will be achieved using descriptive and analysis methods. A major finding of this study shows that Mahmoud al-Warraq relied on three sources of intertextuality: the Holy Qur’an, the Noble Prophet’s Hadith, and the sayings of prominent figures. The study also found two types of intertextuality used: direct and indirect. Keywords: intertextuality - literary criticism – Mahmūd al-Warrāq - The first Abbasid era - poet of wisdom and exhortation. Abstrak Intertekstualiti adalah istilah yang digunakan dalam kritikan sastera untuk membincangkan hubungan antara teks dan kesan terhadap makna teks. Penggunaan intertekstualiti dalam kajian teks dapat membantu untuk memahami faktor-faktor yang mempengaruhi pembinaan teks sastera yang terkandung dalam teks-teks yang lepas. Pengkritik sastera berusaha meneroka intertekstualiti dalam teks dan memperlihatkannya kepada pembaca melalui "proses arkeologi" yang bertujuan untuk meneroka lapisan-lapisan teks yang tersembunyi. Oleh kerana itu, kajian ini cuba menyingkap sumber-sumber intertekstualiti bagi penyair Abbasiyah yang sering menggunakan intertekstualiti dalam puisinya iaitu Mahmud al-Warraq. Kemudian, pengkaji akan mengenal pasti jenis intertekstualiti yang digunakan. Kedua-dua matlamat tersebut akan dicapai menggunakan kaedah deskriptif dan analisis. Di antara hasil kajian ini, Mahmud al-Warraq telah menggunakan tiga sumber intertekstualiti: al-Qur’an al-Karim, al-Hadis al-Nabawi al-Sharif, dan ucapan tokoh-tokoh. Dari segi jenis intertekstualiti pula, beliau menggunakan kedua-dua jenis intertekstualiti; langsung dan tidak langsung. Kata kunci: intertekstualiti – kritikan sastera – Mahmud al-Warraq – era ‘Abbasiyyah yang pertama – penyair hikmah dan nasihat.